Satellite affine formation flying with obstacle avoidance. (December 2019) - Chen, Liangming; Sun, Zhongqi; Li, Chuanjiang; Zhu, Baolong; Wang, Cheng
This paper studies the affine formation control problem for a group of flying satellites with the performance of obstacle avoidance. Assuming that leader satellites can detect the locations of obstacles, we first investigate how to plan advisable trajectories for leader satellites such that they can smoothly pass through some specific types of obstacles by tracking the planned trajectories. Secondly, to enable follower satellites pass through the obstacles by following leader satellites' moving trajectories, a relationship between leader satellites' positions and follower satellites' desired positions is established by employing the affine formation approach. Then, a distributed formation control algorithm is proposed, which ensures all follower satellites converge to their desired positions. Moreover, the uncertainties and disturbances are considered in each satellite's motion dynamics, and are compensated by the designed adaptive laws. Finally, simulation examples are provided to validate the effectiveness of the proposed control algorithms.